2016
DOI: 10.18632/oncotarget.14142
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of RNF2 induces cell cycle arrest and apoptosis in prostate cancer cells through the upregulation of TXNIP

Abstract: RNF2, also known as RING1b or RING2, is identified as the catalytic subunit of polycomb repressive complex 1 (PRC1), which mediates the mono-ubiquitination of histone H2A. RNF2 has been proved to have oncogenic function in many kinds of cancers, but the function of RNF2 in prostate cancer (PCa) has not been evaluated. Here we show that PCa tissues showed higher RNF2 expression than the benign prostatic hyperplasia (BPH) tissues. Knockdown of RNF2 in PCa cells resulted in cell cycle arrest, increased apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 52 publications
(48 reference statements)
0
33
0
Order By: Relevance
“…When tumor was grown at about 3 months, the tumor was taken out and measured in vitro for the comparison of tumor size. Tumor volume was calculated as length × width 2 /2, where the length and width are the longest and shortest axes in millimeters [23]. …”
Section: Methodsmentioning
confidence: 99%
“…When tumor was grown at about 3 months, the tumor was taken out and measured in vitro for the comparison of tumor size. Tumor volume was calculated as length × width 2 /2, where the length and width are the longest and shortest axes in millimeters [23]. …”
Section: Methodsmentioning
confidence: 99%
“…Further ES cell studies revealed that RNF2 target genes repress Wnt signaling [223]. One of the latest in vitro studies showed that knockdown of Rnf2 promotes cell-cycle arrest and apoptosis in prostate cancer cells [233] and gastric cancer cells [234].…”
Section: Core Members Of Ncprcsmentioning
confidence: 99%
“…Thioredoxin‐interacting protein (TXNIP) is the endogenous inhibitor of reactive oxygen species (ROS) elimination, by binding to the active cysteine residue of thioredoxin, resulting in oxidative stress . TXNIP overexpression renders cells more susceptible to oxidative stress and promotes apoptosis . It was reported that downregulation of TXNIP prevented retinal neurodegeneration .…”
Section: Introductionmentioning
confidence: 99%
“…11 TXNIP overexpression renders cells more susceptible to oxidative stress and promotes apoptosis. 12 It was reported that downregulation of TXNIP prevented retinal neurodegeneration. 13 However, research reporting the role of TXNIP in PD is rare.…”
mentioning
confidence: 99%